Genomic location of SSR markers of the potato genetic identity kit. - Ghislain, M.; Herrera, M.R.; Montenegro, J.D. (2013)
Fingerprinting of about 1,700 potato landraces and varieties using 207 simple sequence repeat (SSR) markers led us to identify a group of 24 SSR markers which constitute the potato genetic identity kit used for genetic resource characterization. These markers were selected for single locus, highly polymorphic, and distributed throughout the genome (2 per linkage group). The sequencing of the genome of a doubled-monoploid potato from the Phureja Group has allowed us to characterize better each SSR marker of the PGI kit. These SSR markers were designed originally from DNA sequences from potato varieties originating mostly from the Chilotanum Group. In silico mapping confirmed the physical location as a single locus relative to genetic mapping information for 17 of the 24 SSR markers. One SSR marker [STI0012] was found in two loci of which one corresponds to the expected position according to genetic linkage maps. The SSR marker [STI0004] expected to be located on chromosome VI was located in a superscaffold not yet anchored. One SSR markers [STM0032] was located in a single locus on a different chromosome as expected from genetic mapping information. Finally, 4 SSR markers [STM0019, STM1052, STM1106, and STM5121] were not found anywhere in the genome sequence of the doubled-monoploid potato. This lack of concordance for about 30% of the SSR markers of the PGI kit between physical map and genetic linkage map may be explained by the unfinished status of the potato genome sequence as well as the divergence between these potato taxonomic groups.